THE EFFECT OF PROBLEM BASED LEARNING (PBL) AND STUDENT MATURITY TO LEARNING PERFORMANCE - Dewi Ayunengsih; Johanes Sapri; Turdjai Turdjai (DIADIK, 2017)
student maturity to learning performance. This study using quantitative approach , with experimental quasi method using 2x2 factorial design. The sample of this study are 64 students of 5th grade from SDN 79 Bengkulu city. The technique of collecting data of this study are questionnaire and learning test result. Two-way Anova and t-test used as data technique analysis. The result of this study showed that (1) Student’s learning achievement of science of SDN 79 Bengkulu City who learn using PBL with multimedia is higher than student’s learning performance who learn without multimedia. (2) Student’s learning achievement of science who have high maturity who taught PBL with multimedia is higher than student’s learning performance of science who taught PBL without multimedia.  (3) There is no significant different between student’s learning achievement of science who have low maturity taught using PBL with multimedia and PBL without multimedia. (4) There is interaction effect between PBL model and maturity to student learning achievement. Keywords : pbl learning model, maturity, multimedia, learning achievement